Creativity and Early Childhood Education: studies and research in Italian ECEC contexts - Gariboldi, Antonio; Pugnaghi, Antonella (Revista Eletrônica de Educação, 2024)
Promoting creativity in early childhood education does not only mean encouraging the development of an important capacity for present and future life, but also implies recognizing and assigning value to each child's subjectivity, giving space and attention to his ideas, his judgments and his original processes of learning. In this sense, thinking, promoting and making creativity visible constitutes, from a collaborative and participatory research perspective, three significant keywords of interrelated research areas that allow to study the theme of education to creativity in early childhood. Thinking about creativity refers to the importance of exploring both the ideas of creativity suggested in academic literature, which widen or reduce the definition of such concept through nuances and connotations, and the opinions and representations of teachers and educators. Promoting creativity refers to the examination of more strictly operative aspects, both in terms of the organization of space, materials, time settings and groups, and in terms of the teacher’s role in facilitating and supporting the development of creative processes. Making creativity visible, finally, is about examining the creative processes of children. In this case, it’s about documenting and analysing systematically how children can be creative in different situations and which are the manifestations of their creative thinking.